Interface Engineering for High-Performance and Stable Hybrid Perovskite Shadow-Effect Energy Generator - Chang, Chih-Yu; Chin, Yi-Ling; Huang, Xin-Hao (Chemistry of materials, 2023)
Photovoltaic cells generally suffer a loss of output power due to ubiquitous shadows, which can greatly limit their practical use, especially in metropolitan regions. Very recently, a shadow-effect energy generator (SEG), a new platform that can scavenge energy under shadow conditions, has been demonstrated. In contrast to previously reported SEG based on silicon system, in this study, for the first time, methylammonium lead iodide (MAPbI3) perovskite-based flexible SEG with high-performance and long-term stability is achieved through interface engineering strategy, involving inclusion of atomic-layer-deposited (ALD) Al2O3 and poly{2,5-bis(2-dodecylhexadecyl)-3,6-di(thiophen-2-yl)pyrrolo-[3,4-c]pyrrole-1,4(2H,5H)-dione-alt-(E)-1,2-bis(3-cyanothiophen-2-yl)ethene} (DPP-CNTVT) interfacial layers between the electrode and perovskite layer. The incorporation of the ALD Al2O3 film effectively suppresses the mobile iodide ion-caused electrode corrosion problem and ensures the formation of a Schottky potential barrier. On the other hand, the inclusion of DPP-CNTVT layer can passivate the defects within the perovskite layer and facilitate charge generation and extraction. With all these advantages, the resulting flexible SEG devices exhibit remarkable power density up to 18.22 μW cm–2 under half-in-shadow conditions, which can light up 7 light-emitting diodes and a calculator. To the best of our knowledge, this is the first successful demonstration of perovskite SEG devices, and the power density achieved herein even outperforms that of state-of-the-art silicon-based SEG measured under the same condition. Additionally, through the use of UV-cured epoxy/fluorinated polymer poly(perfluoro(1-butenyl vinyl ether) (CYTOP) bilayer film as the encapsulation layer, long-term stable SEG devices can be realized. Importantly, our strategy has shown great promise for extending the applicability of SEG to flexible semitransparent power sources and self-powered photodetectors. This work provides important guidelines for the exploitation of high-performance and stable perovskite SEG through interface engineering, which sets a new milestone in this field and presents a significant step toward the practical applications of this emerging technology.